2007
DOI: 10.1016/j.jhazmat.2007.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Metal sorption on soils as affected by the dissolved organic matter in sewage sludge and the relative calculation of sewage sludge application

Abstract: To evaluate the influences of sewage sludge-derived organic matters on metal sorption and on the resultant sludge loading estimates, a batch experiment was conducted to compare the sorption of Ni, Cu and Pb in sewage sludge filtrates (1:20 sewage sludge to water) on eight soils and the adsorption of metals in a reference solution which had the same matrix as the sewage sludge filtrate except dissolved organic material (henceforth referred to as reference solution). Metal sorption could be well fitted by linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Wang primarily attributed that pollution to the use of wastewater for irrigation, and proposed that the most contaminated farmland had also been treated with sewage sludge. The observations of Dong et al (2001) are consistent with those of others Hu et al, 2006;Li et al, 2008c;2009b;Liu et al, 2007d;Song et al, 2006b;Wang and Lin, 2003;Wang and Tao, 1998;Wu and Cao, 2010;Zhuang et al, 2009).…”
Section: Downloaded By [Florida Atlantic University] At 01:02 20 Septsupporting
confidence: 79%
“…Wang primarily attributed that pollution to the use of wastewater for irrigation, and proposed that the most contaminated farmland had also been treated with sewage sludge. The observations of Dong et al (2001) are consistent with those of others Hu et al, 2006;Li et al, 2008c;2009b;Liu et al, 2007d;Song et al, 2006b;Wang and Lin, 2003;Wang and Tao, 1998;Wu and Cao, 2010;Zhuang et al, 2009).…”
Section: Downloaded By [Florida Atlantic University] At 01:02 20 Septsupporting
confidence: 79%
“…To date, although many workers have dealt with the adsorption characteristics of dissolved organic matter (DOM) on soil constituents and its effect on metal adsorption and solubility in the soil solution [35,36], there is a lack of information concerning the influence of DOM from the rhizosphere of hyperaccumulating species on heavy metal mobility [15,16]. In the present study, the effect of DOM from the rhizosphere of hyperaccumulator on Zn mobility was investigated by extracting experiment and the results are shown in Fig.…”
Section: The Extracting Ability Of Zn By Dissolved Organic Matter Fromentioning
confidence: 97%
“…Total uptake decreased because Cu 2þ and K þ competed for the active sites of the MCPEs (Peng et al, 2009), thus decreasing the current density. In addition, the copper that was bound to the active sites of the samples can be replaced by the K þ ions through a process of cation exchange, which means that the stability of the complexes that are formed between the samples and Cu(II) can be another factor influencing total uptake (Liu et al, 2007).…”
Section: Behavior Of Copper On the Mcpesmentioning
confidence: 99%
“…Evidence shows that the soils and the biocomposites achieve an equilibrium, while the biosolid does not achieve the equilibrium within the predetermined period of time, which suggests that Cu (II) forms complexes with the active sites of the soils that are more stable than those of the biosolid (Liu et al, 2007). Some authors (Boudesocque et al, 2007;Cheshire et al, 1994;Flogeac et al, 2004) have shown that Cu(II) interacts with the soils and forms "innersphere" complexes where Cu(II) replaces some hydration water molecules of the functional groups, thus forming very stable complexes with the soils, since there is direct coordination between the metal and the functional groups (Palma et al, 2007;Wu et al, 2001).…”
Section: Behavior Of Copper On the Mcpesmentioning
confidence: 99%